Weberian Conflict Theory for Political Dynasty: A Study of Presidential Leadership in the 2024 Indonesian General Elections - Fernando Holqi, Fikri Gali (Advances in Humanities and Contemporary Studies, 2024)
As Head of State, the President is vital in maintaining state sovereignty. However, in the 2024 general election in Indonesia, the President reaped negative sentiments identified as the term "Political Dynasty," which could potentially damage the democratic system. This research aims to identify and analyze the President’s political leadership strategy in the 2024 election by implementing Weberian conflict theory. Actualize the qualitative description approach with the type of literature study. The data collected will be understood, recorded, and analyzed using Weberian conflict theory. Then, conclusions can be drawn with inductive patterns. The study results stated that charismatic leaders in this regard are not just fixated on traditional principles of authority, as Weber argues. However, charismatic leaders are also on formal legal authority (President). The President, in this case, carries out a political strategy to form a political dynasty by using the existence of his charismatic leadership. By maintaining legitimacy rather than democratic principles, this strategy will continue to create conflicts with negative implications for charismatic leaders.